Study of Public and Private Clouds in Indian Environment (International Journal of Engineering and Computer Science, 2014)
The Cloud computing is a general term used to describe a new class of network based computing that take place over the internet. These platform hide the complexity and details of underlying infrastructure from users and applications by providing very simple graphical interface.    Basically, clouds are of three categories.  IT  organizations  can choose  to  deploy  applications  on public,  private,  or  hybrid  clouds. In this paper we are studding Private and Public Cloud